1986
DOI: 10.1177/014662168601000305
|View full text |Cite
|
Sign up to set email alerts
|

The Mokken Scale: A Critical Discussion

Abstract: The Mokken scale is critically discussed. It is argued that Loevinger's H, adapted by Mokken and advocated as a coefficient of scalability, is sensitive to properties of the item set which are extraneous to Mokken's requirement of holomorphy of item response curves. Therefore, when defined in terms of H, the Mokken scale is ambiguous. It is furthermore argued that item-selection free statistical inferences con-ceming the latent person order appear to be insufficiently based on double monotony alone, and that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 10 publications
0
24
0
Order By: Relevance
“…See Mokken (1971) for a thorough review of this nonparametric item response theory model. More recently, several discussions about the usefulness of the Mokken scale analysis haveappeared in the literature (Jansen, Roskam, & Van den Wollenberg, 1984;Roskam, Van den Wollenberg, & Jansen, 1986;Sytsma, 1984Sytsma, , 1986. Further refinements of the model were reported by Molenaar (1982Molenaar ( , 1983a and Sytsma and Molenaar (1987).…”
Section: Further Elaborations and Discussion On The Mokken Scalementioning
confidence: 99%
“…See Mokken (1971) for a thorough review of this nonparametric item response theory model. More recently, several discussions about the usefulness of the Mokken scale analysis haveappeared in the literature (Jansen, Roskam, & Van den Wollenberg, 1984;Roskam, Van den Wollenberg, & Jansen, 1986;Sytsma, 1984Sytsma, , 1986. Further refinements of the model were reported by Molenaar (1982Molenaar ( , 1983a and Sytsma and Molenaar (1987).…”
Section: Further Elaborations and Discussion On The Mokken Scalementioning
confidence: 99%
“…When highly scalable (or high discrimination) items are required, c needs to be high. Coefficient H also tends to be higher when the dispersion of items is larger (Roskam, Van den Wollenberg, & Jansen, 1986). For more information on the effect of c on dimensionality results, see Hemker et al (1995), Molenaar and Sijtsma (2000), and van Abswoude et al (2004).…”
mentioning
confidence: 99%
“…two parameters logistic -modelling difficulty and discrimination only) would have resulted in poorer fit to the data, likely resulting in exclusion of more items. Overall, such exclusions would have led to smaller scales that tend to be less reliable and precise [192]. Finally, the IRSF left asymptotes were all 0, which suggests absence of guessing (i.e.…”
Section: Summary Of Nirt Analysismentioning
confidence: 99%
“…Under the assumption of monotonicity of the IRSF, it has been shown that Hij>0 for all (i,j), and Hi>0 [190], however the reciprocal does not hold, thus Loevinger's Coefficient cannot be used to confirm monotonicity of the IRSF. In addition, Loevinger's Coefficient is sensitive to population variance, item difficulty, discrimination and presence of redundant items in the scale making their interpretation also difficult [191,192]. However, it is commonly accepted that items satisfying Hij>0 for all (i,j), i ≠j,and 0.3<Hi<0.4 form a "weak…”
Section: Score Description Three Months Test-retest and Psychometricmentioning
confidence: 99%
See 1 more Smart Citation